THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON COMPANY BRAND REPUTATION AND PERFORMANCE: A BIBLIOMETRIC ANALYSIS - Koay, Leeng Sze; Govindan, Santhi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study investigates the intellectual landscape and research trends on the impact of Corporate Social Responsibility (CSR) on company brand reputation and performance, a topic of growing importance in both academic and corporate domains. Despite increasing global attention on CSR practices, there remains a limited consolidated understanding of how CSR influences brand equity and firm performance across diverse sectors and regions. To address this gap, we conducted a comprehensive bibliometric analysis using 933 peer-reviewed journal articles retrieved from the Scopus database through advanced search techniques, focusing on the keywords: “corporate social responsibility,” “brand reputation,” and “performance.” The data, spanning from 2001 to 2025, were first processed using Scopus Analyzer to generate descriptive statistics and trend visualizations. Next, Open Refine was employed to clean and harmonize keyword inconsistencies, ensuring dataset accuracy and coherence. To map the conceptual structure and collaborative networks, VOS viewer was used for co-occurrence, co-authorship, and country collaboration analyses. The results identified five major thematic clusters, with “corporate social responsibility,” “sustainability,” and “corporate reputation” as dominant keywords. The United States, China, and the United Kingdom emerged as the most prolific contributors, while the publication trend revealed a significant rise in output post-2015. Co-authorship mapping highlighted increasing international collaboration, especially among developed and emerging economies. The findings contribute to the scholarly understanding of CSR’s strategic role in enhancing organizational outcomes and offer direction for future research by identifying influential themes, authors, and geographic hubs. This study not only provides a comprehensive overview of existing literature but also serves as a valuable reference for academics and practitioners aiming to align CSR with branding and performance objectives.